2020
DOI: 10.1186/s12929-019-0602-1
|View full text |Cite
|
Sign up to set email alerts
|

Human fallopian tube epithelial cells exhibit stemness features, self-renewal capacity, and Wnt-related organoid formation

Abstract: Background: Fallopian tube epithelial cells (FTEC) were thought to be the origin of high-grade serous ovarian carcinoma (HGSOC). Knowledge of the stemness or initiating characteristics of FTEC is insufficient. Previously, we have characterized the stemness cell marker of FTEC, this study aims to further characterize the clonogenicity and spheroid features of FTEC. Methods: We successfully derived FTECs from the epithelial layer of the human fallopian tubes. We examined the morphology, proliferation rate, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…The existence of adult stem/progenitor cells (ASCs) has been reported in the oviduct of humans [ 73 ] and mice [ 74 ]. In both species, spherical oviduct organoids composed of fully differentiated ciliated and secretory OECs (with their apical side towards the lumen) have been successfully generated from sorted and Matrigel © -embedded ASCs [ 73 , 75 , 76 ]. Oviduct organoids can reproduce the in-vivo-like folds of the oviduct epithelium and can be maintained long-term (> 16 months) in culture [ 73 ].…”
Section: Three-dimensional Models Of the Oviduct For The Study Of Thementioning
confidence: 99%
See 1 more Smart Citation
“…The existence of adult stem/progenitor cells (ASCs) has been reported in the oviduct of humans [ 73 ] and mice [ 74 ]. In both species, spherical oviduct organoids composed of fully differentiated ciliated and secretory OECs (with their apical side towards the lumen) have been successfully generated from sorted and Matrigel © -embedded ASCs [ 73 , 75 , 76 ]. Oviduct organoids can reproduce the in-vivo-like folds of the oviduct epithelium and can be maintained long-term (> 16 months) in culture [ 73 ].…”
Section: Three-dimensional Models Of the Oviduct For The Study Of Thementioning
confidence: 99%
“…Oviductal organoids in humans and mice have mostly been used as models to study the origin and development of epithelial ovarian cancers, as the fallopian tube has been implicated as a site of origin of aggressive cancers [ 73 , 75 , 76 ]. In farm animal species, new physiological in vitro 3D models of the oviductal epithelium are needed to understand better the action of systemic regulators (e.g., ovarian steroid hormones) and local cellular interactions with gametes and embryos during the periconception period.…”
Section: Three-dimensional Models Of the Oviduct For The Study Of Thementioning
confidence: 99%
“…Conditioned medium obtained after 24 hours was analyzed for IL-6 levels using ELISA. Cell proliferation of IL-6 overexpressing cells was carried out by XTT, as previously described (Chang et al, 2020). Cells were grown in Roswell Park Memorial Institute medium (RPMI, SigmaAldrich) and supplemented with 1.5% non-essential amino acids, 0.75 % MEM vitamins and 1.5 % sodium bicarbonate.…”
Section: Methodsmentioning
confidence: 99%
“…After deriving fallopian tube epithelial cells from the epithelial monolayer of the human fallopian tube epithelium, Chang et al observed a formation of spheroids in gelatin-coated cultures. Downstream analysis of these spheroids revealed expression of SSEA3 and SSEA4 [ 64 ]. Abundant SSEA4 expression was also noted in the epithelium of benign serous cystadenoma with a gradual decrease towards advanced tumor stage [ 65 ].…”
Section: Globo-series Gslsmentioning
confidence: 99%